Penerapan Model Problem Based Learning Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Di SMP N 13 Kota Bengkulu - Komalasari Sapitri; Hilyati Milla; Meirani Meirani (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This research aims to find out what critical thinking skills are part of the learning process in class in social science subjects at SMP 13 Bengkulu city. The method used in this research is a qualitative method by researchers without any intermediaries. Data obtained through direct observation of students and teachers at SMP 13 Bengkulu City. The secondary data used are written sources such as the problem studied, namely the application of the problem based learning model in strengthening students' critical thinking skills at SMP N 13, Bengkulu City. . Data collection uses observation, documentation. Data analysis consists of data collection, drawing conclusions. Based on the results of research at SMP N 13 Bengkulu City, learning was carried out in the classroom.